Pelatihan Penciptaan Musikalisasi Puisi sebagai Bentuk Apresiasi Sastra pada Siswa SMK Telkom Pekanbaru - Essy Syam; Qori Islami Aris (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2021)
Scientific articles are scientific papers of research results communicated in scientific publications, such as journals, magazines, or other publications. In schools, especially teachers who teach Bahasa Indonesia, are required to be able to motivate students to increase their reading interest in literature, because by studying literature students can get various benefits for their lives. Therefore, a teacher is required to be able to guide students to give appreciation for literary works, especially poetry. However, the reality in the field, teachers have difficulty teaching poetry musicalization. Because in addition to a calm understanding of literature itself, an understanding of music is also very important. This Community Service Activity aims to provide students with understanding and provide provisions for the ability to create poetry musicalization as an alternative in appreciating literature, especially poetry. The method used in this activity is in the form of workshops delivered with lectures, question-and-answer, and practical techniques. To find out the extent of student acceptance and understanding, as well as student abilities, at the beginning and end of the training an assessment or evaluation is carried out by filling out the pretest and posttest sheets. Based on the results of the tests that have been conducted, it is known that the participants experienced an increase in their understanding of the concepts of literary appreciation, poetry appreciation, and poetry musicalization from 64% to 100%. Starting from this understanding, students can be more creative in creating a poetry musicalization. Keywords: Literary Appreciation, Poetry Appreciation, Poetry Musicalization